2009
DOI: 10.1002/uog.6439
|View full text |Cite
|
Sign up to set email alerts
|

Use of Z‐scores to select a fetal biometric reference curve

Abstract: Objective Fetal biometric data are a major part of prenatal ultrasound screening in the general population. The aim of this study was to analyze the effect of choice of reference curve on the quality of screening for growth abnormalities, using a statistical tool based on Z-scores. Methods The biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC) and femur length (FL) were measured in 9699 ultrasound scans during the second trimester (20-24 weeks of gestation) and 8100 scans during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
4
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 19 publications
(34 reference statements)
1
25
4
3
Order By: Relevance
“…Similar observations were made in the previous studies [4,11,13,14,16,17,18,19,20]. Accurate pregnancy dating is important to establish gestational age for evaluation of fetal growth and prediction of the date of delivery.…”
Section: Discussionsupporting
confidence: 84%
“…Similar observations were made in the previous studies [4,11,13,14,16,17,18,19,20]. Accurate pregnancy dating is important to establish gestational age for evaluation of fetal growth and prediction of the date of delivery.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings were consistent, although the risk estimates and ORs were slightly lower when using our own reference curve. We suggest that a cut‐off value closer to –2SD instead of the 5 th percentile should be considered, given an appropriate reference curve.…”
Section: Discussionmentioning
confidence: 99%
“…With Levene's test, we showed that the variability among the measurements over the course of pregnancy was slight, and, after calculating the residuals, Z-score estimation became possible. In view of the applicability of Z-scores to public health, calculating them is important as this is a good method for expressing biometric measurements and for selecting the reference curve that best corresponds to a given population [17]. Moreover, our group has had recent experience using Z-scores for constructing reference ranges for fetal cardiac volume [18].…”
Section: Discussionmentioning
confidence: 99%